2013
DOI: 10.1007/s00705-013-1606-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel cyclovirus discovered in the Florida woods cockroach Eurycotis floridana (Walker)

Abstract: A novel cyclovirus (proposed genus "Cyclovirus", family Circoviridae) was discovered in a specimen of Eurycotis floridana (Walker), also known as the Florida woods cockroach or palmetto bug, collected from Tarpon Springs, Florida. The Florida woods cockroach-associated cyclovirus GS140 (FWCasCyV-GS140) was obtained through a degenerate PCR assay and showed 64 % genome-wide pairwise identity to a cyclovirus identified in bat feces. This finding supports recent reports suggesting that Circoviridae members, tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Recent metagenomic studies have identified a number of cycloviruses from the faeces, respiratory tract, CSF and sera of humans, and in bat faeces, chimpanzee faeces, muscle tissues of chickens, cows and goats, and in insect abdomens (Dayaram et al, 2013;Ge et al, 2011;Li et al, 2010aLi et al, , b, 2011aPadilla-Rodriguez et al, 2013;Phan et al, 2014;Rosario et al, 2011;Smits et al, 2013b;Tan et al, 2013). Consistent with the wide range of host animals, we found a high incidence of cycloviruses in shrews.…”
Section: Discussionmentioning
confidence: 99%
“…Recent metagenomic studies have identified a number of cycloviruses from the faeces, respiratory tract, CSF and sera of humans, and in bat faeces, chimpanzee faeces, muscle tissues of chickens, cows and goats, and in insect abdomens (Dayaram et al, 2013;Ge et al, 2011;Li et al, 2010aLi et al, , b, 2011aPadilla-Rodriguez et al, 2013;Phan et al, 2014;Rosario et al, 2011;Smits et al, 2013b;Tan et al, 2013). Consistent with the wide range of host animals, we found a high incidence of cycloviruses in shrews.…”
Section: Discussionmentioning
confidence: 99%
“…Although cycloviruses were discovered in stool samples from primates [34], cyclovirus genomes have now been reported from a diversity of specimens including mammals (bats, cats, cows, goats, horses, squirrels, sheep) [18,34,36,38,43,49,73,91,92], birds (chickens) [34,36], and insects (cockroaches and dragonflies) [11,59,70,71] (Table 1). Additionally, a diversity of cyclovirus genomes have been recovered from human samples other than faeces [17,34,80], including cerebrospinal fluid [80], blood serum [76], and respiratory b Fig.…”
Section: Sqacyv-1 Lc018134 Callosciurus Erythraeus Thaiwanensismentioning
confidence: 99%
“…Genetically highly diverse cycloviruses were initially found in the faeces of Pakistani children with and without acute flaccid paralysis (Victoria et al, 2009), in wild chimpanzees (Li et al, 2010) and in tissues of farm animals including cows, goats, bats and chickens (Ge et al, 2011;Li et al, 2010Li et al, , 2011. Unexpectedly, other cyclovirus species have also been detected in insects, namely dragonflies and cockroaches (Dayaram et al, 2013;Padilla-Rodriguez et al, 2013;Rosario et al, 2011). In 2013, a cyclovirus species (CyCV-CN) was found initially using viral metagenomics and then by PCR in 4 % of cerebrospinal fluid (CSF) specimens from Vietnamese children with unexplained central nervous system disorder, but not in CSF from patients with non-neurological problems, as well as in 4.2 % of faeces from healthy Vietnamese children (Tan et al, 2013).…”
mentioning
confidence: 99%